Corrosion behaviour of steel during accelerated carbonation of solutions which simulate the pore concrete solution - Alonso, C.; Andrade, C. (Materiales de Construcción, 1987)
In spite of the numerous studies carried out on carbonation of the concrete, very few data have been published on the mechanism of steel depassivation and the corrosion rates involved in this type of phenomenon. Also some uncertainties remain as to the chemical composition of the pore solution of a carbonated concrete.Random behaviours related with the changes in the corrosion rate of steel during accelerated carbonation of cement mortars have suggested the need to study the process in a more simple medium which allows the isolation of the different parameters. Thus, saturated Ca(0H)2 -base solutions with different additions of KOH and NaOH have been used to simulate the real pore concrete solution.In the present work, simultaneous changes in the pH value, corrosion potential and corrosion rate (measured by means of the determination of the Polarization Resistance) of steel roads have been monitored during accelerated carbonation produced by a constant flux through the solution of CO2 gas and/or air.